Autotaxin interacts with lipoprotein(a) and oxidized phospholipids in predicting the risk of calcific aortic valve stenosis in patients with coronary artery disease. (30th May 2016) - Nsaibia, M. J.; Mahmut, A.; Boulanger, M.‐C.; Arsenault, B. J.; Bouchareb, R.; Simard, S.; Witztum, J. L.; Clavel, M.‐A.; Pibarot, P.; Bossé, Y.; Tsimikas, S.; Mathieu, P.
Abstract: Background: Studies have shown that lipoprotein(a) [Lp(a)], an important carrier of oxidized phospholipids, is causally related to calcific aortic valve stenosis (CAVS). Recently, we found that Lp(a) mediates the development of CAVS through autotaxin (ATX). Objective: To determine the predictive value of circulating ATX mass and activity for CAVS. Methods: We performed a case‐control study in 300 patients with coronary artery disease (CAD). Patients with CAVS plus CAD (cases, n = 150) were age‐ and gender‐matched (1 : 1) to patients with CAD without aortic valve disease (controls, n = 150). ATX mass and enzymatic activity and levels of Lp(a) and oxidized phospholipids on apolipoprotein B‐100 (OxPL‐apoB) were determined in fasting plasma samples. Results: Compared to patients with CAD alone, ATX mass ( P < 0.0001), ATX activity ( P = 0.05), Lp(a) ( P = 0.003) and OxPL‐apoB ( P < 0.0001) levels were elevated in those with CAVS. After adjustment, we found that ATX mass (OR 1.06, 95% CI 1.03–1.10 per 10 ng mL −1, P = 0.001) and ATX activity (OR 1.57, 95% CI 1.14–2.17 per 10 RFU min −1, P = 0.005) were independently associated with CAVS. ATX activity interacted with Lp(a) ( P = 0.004) and OxPL‐apoB ( P = 0.001) on CAVS risk. After adjustment, compared to patients with low ATX activity (dichotomized at the median value) and low Lp(a) (<50 mg dL −1 ) or OxPL‐apoB (<2.02 nmol L −1, median) levels (referent), patients with both higher ATX activity (≥84 RFU min −1 ) and Lp(a) (≥50 mg dL −1 ) (OR 3.46, 95% CI 1.40–8.58, P = 0.007) or OxPL‐apoB (≥2.02 nmol L −1, median) (OR 5.48, 95% CI 2.45–12.27, P < 0.0001) had an elevated risk of CAVS. Conclusion: Autotaxin is a novel and independent predictor of CAVS in patients with CAD.